Juggling reveals a decisional component to tactile suppression. - Juravle, G; Spence, C (2011)
Goal-directed movements are characterized by sensory suppression, that is, by decreased sensitivity to tactile stimuli. In the present study, we investigated tactile suppression during movement using a complex motor task: basic 3-ball juggling. It was hypothesized that a decrease in tactile sensitivity would be observed, together with a shift in participants' response bias while juggling. In a first experiment, participants had to detect a short gap in an otherwise continuous vibratory stimulus, which was delivered to their wrist under conditions of rest or else while juggling. In a second experiment, participants detected a short time gap in a continuous auditory signal, under the same conditions. In a final control experiment performed at rest, participants detected a short time gap in an auditory or tactile signal. In an additional condition, the detection of a gap in tactile stimulation was required under conditions of intramodal tactile interference. Participants were significantly less sensitive to detect a gap in tactile stimulation whilst juggling. Most importantly, these results were paired with a significant shift toward participants adopting a more conservative criterion when responding to the presence of the gap (i.e. they were more likely to say that a gap was not present). Taken together, these results demonstrate movement-related tactile sensory suppression and point to a decisional component in tactile suppression, thus suggesting that tactile suppression could already be triggered in the brain ahead of the motor command.